A review of microplastics in soil: Occurrence, analytical methods, combined contamination and risks - Zhang, Zhiqin; Zhao, Shuling; Chen, Li; Duan, Chengjiao; Zhang, Xingchang; Fang, Linchuan (Environmental pollution (1987), 2022)
Microplastics (MPs) pollution is becoming a serious environmental issue of global concern. Currently, the effects of MPs on aquatic ecosystems have been studied in detail and in depth from species to communities. However, soils, the largest reservoir of MPs, have been less studied, and little is known about the occurrence, environmental fate and ecological impacts of MPs. Therefore, based on the existing knowledge, this paper firstly focused specifically on the main sources of soil MPs pollution and explored the main reasons for their strong heterogeneity in spatial distribution. Secondly, as a primary prerequisite for evaluating MPs contamination, we systematically summarized the analytical methods for soil MPs and critically compared the advantages and disadvantages of the different methods in the various operational steps. Furthermore, this review highlighted the combined contamination of MPs with complex chemical contaminants, the sorption mechanisms and the associated factors in the soil. Finally, the risks posed by MPs to soil, plants, the food chain and even humans were outlined, and future directions for soil MPs research were proposed, while the urgent need for a unified approach to MPs extraction and identification was emphasized. This study provides a theoretical reference for a comprehensive understanding of the separation of soil MPs and their ecological risk as carriers of pollution. •Soil microplastics (MPs) are ubiquitous and spatial distribution varies widely.•We summarized and compared the methods for the analysis of soil MPs.•We emphasized the co-contamination, influencing factors and effects of MPs and chemicals.•MPs pose potential impacts on soil ecosystems, plants and human food chains.